Regional differences in quality of krill and fish as prey along the Western Antarctic Peninsula - Ruck, Kate E.; Steinberg, Deborah K.; Canuel, Elizabeth A. (Marine Ecology Progress Series, 2014)
The warming trend in the northern part of the Western Antarctic Peninsula (WAP) has led to a decrease in perennial and summer sea ice, an increase in heat content over the shelf, and lower phytoplankton biomass, which could affect the prey quality of krill and fish that are utilized by apex predators. We compared prey quality metrics, including elemental (C, N) content; total, neutral, and polar lipid content; and energy densities of known penguin prey items including krill (Euphausia superba, Thysanoessa macrura, and E. crystallorophias) and fish (silverfish Pleuragramma antarcticum and the myctophid Electrona antarctica) along the WAP latitudinal gradient each January from 2009 to 2011. E. antarctica had the highest prey quality in terms of lipid content and energy density, followed by T. macrura and P. antarcticum, then E. crystallorophias and E. superba. For all species, variations in C and N content were most strongly correlated with the animals’ neutral lipid content, in that animals with the larger neutral lipid stores had significantly higher C and lower N content. Across all sexes and maturity stages, E. superba in the southern study region had ca. 20% higher total lipid content than E. superba in the north, and a stepwise multiple linear regression analysis showed that latitude, sexual differences, and upper water column temperatures best explained this regional difference in lipid content. This regional variability in E. superba prey quality could affect the ability of apex predators that rely on E. superba to meet their energetic demands, and should be considered in future modeling efforts.